Investigation of Intestinal Parasites in Stray Cats - Zangana, Dr. Ashraf Jamal Mahmoud (Journal of Science in Medicine and Life, 2025)
The study included collecting fecal samples from stray cats in Tikrit / Salah al-Din Governorate for the period from October 2022 until the end of January 2023. The total number of samples taken from fecal samples of stray cats in home gardens and public parks in Tikrit city was 87 samples, including 26 positive samples with an infection rate of 29.88%. The cystic stages of the animal protozoa Coccidia and Toxoplasma gondii were diagnosed in the feces of some stray cats at percentages of 8.04% and 11.49%, respectively, and at a rate of 6.89% for Toxocara cati, and Ancylstoma eggs at a rate of 3.44%.